Parental Educational Level and Increase in Street Children in Calabar Metropolis, Cross River State, Nigeria - Edinyang, S. D.; Opoh, Frederick Awhen; Odey, Edward Ogar; Ushie, Doris; Adams, Amina Odugbo (Richtmann Publishing, 2020)
This study examined the influence of parental educational level on the increase in street children in Calabar metropolis of Nigeria. Single speculation was defined to control the investigation. A writing survey was done dependent on the attribute under investigation. An approved four 16 ounces Likert scale questionnaire was utilized for assessment. The findings revealed that there is a significant influence of parental educational level on the increase in street children in Calabar Metropolis.